ASSESSMENT OF PUBLIC KNOWLEDGE AND ATTITUDE REGARDING ANTIBIOTIC USE IN A TERTIARY CARE HOSPITAL - P, Chandrakanth; TS, Mohamed Saleem; Mohan Reddy, Madhan; C, Gopinath; Rao, Madhan Mohan (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: The present study was designed to investigate the public knowledge and attitude toward antibiotic use in a general population visiting the tertiary care hospital. Methods: A prospective cross-sectional survey conducted for a period of 6-month December-2013 to May-2014. Knowledge scoring was given based on the percentage of correct responses. Data were collected using a self-prepared questionnaire and analyzed using descriptive statistics. Association of respondent's knowledge score with sex, age group, educational level, and income was analyzed by Chi-square test. Results: The results of our study showed that the level of knowledge on antibiotics use was poor in 117 (65%) of the study population who had given <50% correct response. The current study showed that there was a significant difference in knowledge between education level groups (pâ‰¤0.0001). The other responses regarding knowledge are 27.2% accepted that antibiotics are indicated for relieving pain and inflammation, 45% of participants thought that antibiotics are the drugs indicated to reduce fever. About 76.6% of respondents had administered antibiotics without a doctor's prescription, 44% of respondents used antibiotics with their friends and family member's suggestions. 48% of respondents keep antibiotics stock at home for future use and 79.4% of respondents keep leftover antibiotics for personal future use, 31% share their antibiotics with family members when they are sick and 34% of respondents use leftover antibiotics for a respiratory illness. Conclusion: Patients, as well as healthcare professionals, have a major role to play in attaining rational antibiotic use. Antibiotic awareness campaigns and patient counseling should promote specific messages to public members from the high riskâ€ groups, to fill up the knowledge and attitude gaps. Keywords: Antibiotic use, Self-medication, Attitude, Miss-use, Awareness, Microbial resistance.